2012
DOI: 10.5688/ajpe767135
|View full text |Cite
|
Sign up to set email alerts
|

An Introductory Review Module For an Anti-Infectives Therapeutics Course

Abstract: Objective. To determine whether an introductory review module using a hybrid-learning approach helped students learn infectious disease management in an anti-infectives therapeutics course.Design. An introductory module consisting of an online pharmacology review, pre-class assignment, 2 classroom lectures, and 1 case-based lecture was developed and implemented. Assessment. Among the 110 students who completed pre-and post-tests on the material covered, average scores increased from 71% to 83% ( p,0.0001). Per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…This teaching strategy has been well received by students, with increased student preparation for in-class discussion and improved test performance. [5][6][7][8][9][10] Screencasting is a type of e-lecture that incorporates digital recording of computer screen actions with dubbed audio narration. For example, an instructor can record voice-over narration for Powerpoint slides to create an e-lecture that can be posted in a video format for students to view.…”
Section: Introductionmentioning
confidence: 99%
“…This teaching strategy has been well received by students, with increased student preparation for in-class discussion and improved test performance. [5][6][7][8][9][10] Screencasting is a type of e-lecture that incorporates digital recording of computer screen actions with dubbed audio narration. For example, an instructor can record voice-over narration for Powerpoint slides to create an e-lecture that can be posted in a video format for students to view.…”
Section: Introductionmentioning
confidence: 99%
“…In conjunction with the result of the research, previous pre-class assignment researches that involved long term implementation (He, 2016;Stang et al, 2016;Kung, 2016;Kuo, 2016;Miller et al, 2018) and short term implementation (Leonard et al, 2012;Azizifar et al, 2015;Haque, 2010;Gouia and Gunn, 2016) of pre-class assignment on learners with no prior exposure to pre-class assignment all showed a positive result. Hence, the pre-class assignment is strongly proven to have no relation with whether the learners have prior exposure to pre-class assignments or not.…”
Section: Discussion and Recommendationsmentioning
confidence: 51%
“…Some negative student attitudes have been reported towards the online component of hybrid coursework, due to students' perceived extra time demands by instructors (Leonard et al, 2012). In the authors' study where online activities were deemed as not helpful in the feedback, the reason was not given.…”
Section: Student Engagementmentioning
confidence: 88%
“…Several studies report utility with blended or hybrid learning, and positive impact on student learning (Novak et al, 1999;Zapantis et al, 2008;Congdon et al, 2009;Crouch, 2009;Leonard et al, 2012). Crouch's work (2009) revealed that blended learning was instrumental in improving student preparation prior to attending class and long term knowledge retention.…”
Section: Student Engagementmentioning
confidence: 99%